When Does Aftermarket Monopolization Soften Foremarket Competition?. Issue 4 (21st March 2016) - Fong, Yuk‐fai; Li, Jin; Liu, Ke
Abstract : This paper investigates firms' abilities to tacitly collude when they each monopolize a proprietary aftermarket. When firms' aftermarkets are completely isolated from foremarket competition, they cannot tacitly collude more easily than single‐product firms. However, when their aftermarket power is contested by foremarket competition as equipment owners view new equipment as a substitute for their incumbent firm's aftermarket product, profitable tacit collusion is sustainable among a larger number of firms. Conditions under which introduction of aftermarket competition hinders firms' ability to tacitly collude are characterized.